Cligosiban, A Novel Brain-Penetrant, Selective Oxytocin Receptor Antagonist, Inhibits Ejaculatory Physiology in Rodents. Issue 12 (1st December 2018) - Wayman, Chris; Russell, Rachel; Tang, Kim; Weibly, Laura; Gaboardi, Samantha; Fisher, Lucy; Allers, Kelly; Jackson, Margaret; Hawcock, Tony; Robinson, Nicola; Wilson, Lesley; Gupta, Julie; et al.
Abstract: Introduction: Few treatments are available for men with premature ejaculation (PE); oxytocin (OT) receptor antagonism in the central nervous system (CNS) is a potential new approach. Aim: To determine if cligosiban selectively inhibits human OT receptors, penetrates the CNS, shows pharmacology in the CNS, and effects ejaculatory physiology in pre-clinical systems. Methods: Experiments complied with United Kingdom legislation and were subject to local ethical review. In vitro potency and selectivity of cligosiban was assessed using recombinant and native OT receptor systems including both neuronal and non-neuronal cell types. Selectivity was determined over neighboring V1A, V1B, and V2 vasopressin receptors using a combination of recombinant and native vasopressin receptor assay systems. To determine an effect on central OT receptors and on ejaculation, cligosiban was evaluated in 2 anesthetized rat models—the electromyography model of ejaculatory physiology and a model of OT-mediated CNS neuronal firing. The CNS penetration of cligosiban was also determined by measuring cerebrospinal fluid and plasma drug concentrations following an intravenous (IV) infusion in rats. Main Outcome Measure: These were functional measures of pharmacology in vitro, in cell lines and tissues, and in vivo in rats. Results: Cligosiban is a potent OT receptor antagonist, with a base dissociation constant of 5.7 nmol/L against native human uterine smooth muscle cell OT receptors. Cligosiban displays similar antagonistic potency against human recombinant and rat native OT receptors, including neuronal OT receptors. Cligosiban demonstrates >100-fold selectivity over human V1A, V1B, and V2 vasopressin receptors. In the electromyography model, cligosiban (0.9 mg/kg, IV bolus) reduced the bulbospongiosum burst pattern and contraction amplitude associated with ejaculation. In the anesthetized CNS neuronal firing model, the same dosing regimen of cligosiban (0.9 mg/kg IV bolus) modulated the OT-mediated response in the nucleus tractus solitarius. After systemic dosing to rats, cligosiban showed good CNS penetration. Clinical Implications: As the first highly selective and centrally penetrant OT receptor antagonist, cligosiban represents a promising compound to test the clinical hypothesis that antagonism of central OT receptors may be of therapeutic benefit in the treatment of PE. Strength & Limitations: The pharmacology and selectivity of cligosiban is determined using functional assays in recombinant cell lines, native cell lines, and tissue. Functional outcomes in in vivo systems are linked to CNS measures of pharmacology. The translation of the animal models of ejaculation to PE in man is unproven. Conclusion: Cligosiban, a potent, selective OT receptor antagonist, demonstrated CNS penetration and pharmacology and, using the same dosing regimen, inhibited apomorphine-induced ejaculation in rats. Cligosiban is a promising compound to test the clinical hypothesis that antagonism of central OT receptors may be of therapeutic benefit in the treatment of PE.